Beyond Complex Trauma: An Existential View of Adverse Childhood Experiences. Issue 3 (8th October 2018) - Zyromski, Brett; Dollarhide, Colette T.; Aras, Yahyahan; Geiger, Sarah; Oehrtman, J. P.; Clarke, Halley
Abstract : Adverse childhood experiences (ACEs) can trigger a variety of existential reactions that disrupt physical, mental, and behavioral health. This article explores the implications of ACEs for the development of children, adolescents, and adults. Examining ACEs through an existential lens, the authors provide a way to conceptualize clients with multiple ACEs and offer suggestions for interventions.